JURASSIC TECTONICS OF NORTH CHINA: A SYNTHETIC VIEW - Zhang Y.; Zhang T.; Dong S.; Zhao Y. (My University, 2007)
This paper gives a synthetic view on Jurassic tectonics of North China, with an attempt to propose a framework for stepwise tectonic evolution history. Jurassic sedimentation, deformation and magmatism in North China have been divided into three stages. The earliest Jurassic is marked by a magmatism gap in 205-190 Ma and regional uplift, which are considered to be the continuation of the "Indosinian Movement" tectonic period characterized by continent-continent collision between the NCB and the SCB. Early to Middle Jurassic (190-170 Ma) was dominated by weak lithospheric extension expressed by mantle derived plutonism and volcanism along the Yanshan belt and alongside the Tan - Lu fault zone, normal faulting and graben formation along the Yinshan-Yanshan tectonic belt, depression and resumation of coal-bearing sedimentation in vast region of the NCB. Middle to Late Jurassic stage (from 165±5 Ma to 136 Ma) was dominated by intensive intraplate deformation resulting from multi-directed compressions. At least two major deformation events have been identified: one is marked by stratigraphic unconformity beneath thick Upper Jurassic molasic series in the foreland zones of the western Ordos thrust and fold belt and along the Yinshan-Yanshan belt and predated to 160 Ma; the other one is indicated by stratigraphic unconformity at the base of Lower Cretaceous and predated to 135 Ma. During this last stage, two latitudinal tectonic belts, the Yinshan-Yanshan one to north and the Qinling - Dabie one to south, and the western margin of the Ordos basin were all activated by thrusting; the NCB itself was deformed by NE to NNE-trending structural system involving thrusting, associated folding and sinistral strike-slip faulting, which were spatially partitioned. Foliated S-type granitic plutons aged 160-150 Ma were massively emplaced in the Jiao-Liao region east of the Tan-Lu fault zone and indicate important crustal thickening in the eastern part of North China. Jurassic deformation patterns, different tectonic systems and multi-directed contractions in North China recorded far-field effects of synchronous convergences, toward the east Asian continent, of three different plates, the Siberian in north, the paleo Pacific in east and the Lhasa Block in southwest. This Middle to Late Jurassic intraplate orogenesis and pervasive shortening deformation preceded lithospheric attenuation and thinning in East China, which most possibly started by the Earliest Cretaceous around 135 Ma.
Keywords: CONVERGENT TECTONIC SYSTEM; INTRAPLATE DEFORMATION; JURASSIC TECTONICS; MULTI-DIRECTIONAL COMPRESSIONS; NORTH CHINA; Cretaceous; Jurassic; Mesozoic::Cretaceous; Мезозой::Меловая; Mesozoic::Jurassic; Мезозой::Юрская